Karakteristik Nyeri Kepala pada Anak dan Remaja: A Literature Review - Silma Nuraini; Roro Rukmi Windi Perdani; Terza Aflika Happy; Prambudi Rukmono (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Headache is one of the most common neurological complaints in children and adolescents, with a prevalence that increases with age. Clinical manifestations in this population often differ from those in adults, creating challenges in diagnosis and management. This literature review aims to evaluate the classification, clinical characteristics, triggering factors, and impact of headache in the 6–18-year age group based on the most recent scientific evidence. The review was conducted using a narrative approach by searching the PubMed, Google Scholar, and ScienceDirect databases for studies published within the past ten years, with priority given to the use of the International Classification of Headache Disorders (ICHD-3) criteria. The literature indicates that tension-type headache (TTH) and migraine are the most predominant subtypes. Pediatric-specific characteristics include shorter attack durations (2–72 hours) and predominantly bilateral pain localization. Triggering factors are multifactorial, encompassing academic stress, excessive screen time, sleep disturbances, and hormonal fluctuations in adolescent girls. Headache has a significant impact on school absenteeism and overall quality of life. Recognizing the unique characteristics of headache in children is essential to avoid misdiagnosis. Management approaches should be holistic, incorporating the identification of red flags, lifestyle modifications, and the management of comorbidities to prevent progression to chronic headache into adulthood.